The characteristics of methane adsorption capacity and behavior of tectonic coal - Zhang, Hang; Zhang, Xiaobing; Zhang, Yugui; Wang, Zhenzhi (Frontiers in Earth Science, 2023)
Abstract: Tectonic coal reserach is an important content to gas disaster prevention and coalbed methane (CBM) exploration in outburst coal seams. Many projects, such as adsorption difference between tectonic coal and its untectonic coal, adsorption evaluation of tectonic coal, factors for adsorption capacity of tectonic coal, gas-solid coupling feature in tectonic coal and supercritical adsorption phenomena of tectonic coal, were carried out by scientists. Combined with a long-term study on organic matter structure and methane adsorption of tectonic coal, the author summarized recent-years’ researches on adsorption of tectonic coal-methane at home and abroad from the dispute of adsorption ability determination, the methane adsorption feature via structure-property relationship, the thermodynamic characterization of methane adsorption behavior, quantum chemical calculation of the adsorption and the gas content calculation based on loss compensation, respectively. The research has a reference to fine research of coal adsorption and CBM exploration practices.